Relative and Global Health: A Comparative Study between Healthcare Systems of Jordan and France - Aladeen Alloubani, Ibrahim Mbarak Abdelhafiz and Abdulmoneam A. Saleh (World Health & Population, 2016)
Objective: This relative study includes categorical exploration of the economics, demographic, political, social and financial data to realize the basic reasons of the present healthcare systems in these countries. Methods: Descriptive and comparative methods were used. This study tries to relate the healthcare systems of Jordan with that of France to produce effective lessons that can be helpful for guiding future developments down the correct path. Results: Depending on many factors such as life expectancy, the mortality rate in infants, universal medical coverage and availability of healthcare services to the masses, significant disparities between the two systems were found. Conclusion: Through this study, it has been concluded that the healthcare system of Jordan has a lot to improve with regard to standards of services offered, and there are many aspects to be learned from the French healthcare system by the Jordanian one, including the healthcare coverage system and the cost-sharing strategies.
Keywords: Healthcare System, Quality, Insurance, France, Jordan